2013
DOI: 10.6000/1929-4247.2013.02.01.5
|View full text |Cite
|
Sign up to set email alerts
|

Blood Cu/Zn Ratio in Children of School Age, Living in Malaria Endemic Area in Abidjan (Côte D'ivoire)

Abstract: Background: Food intake contains various nutrients which the loss or destruction are exogenous factors of oxidative damages in our body, aggravated by infectious diseases. Blood ratio Cu/Zn is an indicator about the pool of defenses anti oxidizing to measure damage oxidative. The present study aimed to investigate the blood ratio Cu/Zn an indicator of pool of oxidative stress and eating risk factors in children school age, living in malaria endemic area.Methods: A total of 113 participants, aged 5-14 years wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Although Laine et al (2020), in middleaged and older men, suggested that the serum Cu level alone might be a better marker for future risk of an infection [13], other authors believe that the Cu/Zn ratio is a wellestablished feature of infections [14], including parasitic infections, such as Schistosoma mansoni, Enterobious vermicularis, and Trypanosoma cruzi infections and in giardiasis [15] or amebiasis [15,16] and tuberculosis (TB) [14,17]. The significantly higher Cu/Zn ratio at baseline in giardiasis and amebiasis [16], malaria [18], and TB [19] returned to normal after therapy. Furthermore, this Cu/Zn ratio has a diagnostic value in several human disorders [14].…”
Section: Introductionmentioning
confidence: 99%
“…Although Laine et al (2020), in middleaged and older men, suggested that the serum Cu level alone might be a better marker for future risk of an infection [13], other authors believe that the Cu/Zn ratio is a wellestablished feature of infections [14], including parasitic infections, such as Schistosoma mansoni, Enterobious vermicularis, and Trypanosoma cruzi infections and in giardiasis [15] or amebiasis [15,16] and tuberculosis (TB) [14,17]. The significantly higher Cu/Zn ratio at baseline in giardiasis and amebiasis [16], malaria [18], and TB [19] returned to normal after therapy. Furthermore, this Cu/Zn ratio has a diagnostic value in several human disorders [14].…”
Section: Introductionmentioning
confidence: 99%
“…Cu/Zn ratio serves to be an important indicator to assess the level of oxidative stress in case of infectious disease 4,5 and was found to be significantly higher in the serum of tuberculosis patients in several studies. [6][7][8][9][10] Though various studies has been conducted worldwide regarding the role of serum Cu/Zn ration in active pulmonary tuberculosis but very less studies were done from north Indian population and till date no studies was reported on smear negative pulmonary tuberculosis patients.…”
Section: Introductionmentioning
confidence: 99%
“…Among these micronutrients, zinc and copper play an important role in the proliferation and differentiation of cells of innate and acquired immunity [9]. Moreover, the Cu / Zn ratio is an indicator for assessing the level of oxidative stress in the case of infectious diseases in general [10, 11]. These two micronutrients play an essential role in resistance to certain infectious diseases like tuberculosis [12].…”
Section: Introductionmentioning
confidence: 99%